2018
DOI: 10.1007/s00264-018-3891-1
|View full text |Cite
|
Sign up to set email alerts
|

Reverse total shoulder arthroplasty using helical blade to optimize glenoid fixation and bone preservation: preliminary results in thirty five patients with minimum two year follow-up

Abstract: The helical blade provides a satisfactory primary fixation. Because of its length (21 mm), care should be taken in cases of pre-existing bone loss or sclerotic bone to avoid glenoid fracture or anterior cortical perforation. Helical blade has the potential to facilitate glenoid implant revision by preserving the glenoid bone stock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Subscapularis repair was studied in four articles [ 14 , 19 , 29 , 48 ]. Sixteen studies included intraoperative stem cementation data; of 1508 cases, 398 stems were cemented (26.4%), and six studies reported press-fit stems [ 23 , 26 , 31 , 44 , 45 , 50 ] only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subscapularis repair was studied in four articles [ 14 , 19 , 29 , 48 ]. Sixteen studies included intraoperative stem cementation data; of 1508 cases, 398 stems were cemented (26.4%), and six studies reported press-fit stems [ 23 , 26 , 31 , 44 , 45 , 50 ] only.…”
Section: Resultsmentioning
confidence: 99%
“…Instability (29 dislocations out of 3634 cases) had a mean incidence of 0.8% in 25 studies concerning complications. A total of seven studies including 631 RSA did not record any dislocation [ 24 , 26 , 27 , 32 , 41 , 45 , 50 ]. The role of subscapularis repair in instability was investigated in four studies[ 14 , 19 , 29 , 48 ], with a total of 986 arthroplasties: seven dislocations occurred in 445 nonrepaired subscapularis (1.6% rate) and two dislocations in 541 repaired tendons RSA (0.4% rate).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-six studies 15,46,66,69,119-134,134157 reported a total of 188 intraoperative fractures (IFx) among the complications, representing a global IFx rate of 1.4%.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with osteoporosis, care must be taken during reaming and impaction of the baseplate. In addition, in patients with degenerative osteoarthritis, the glenoid can be fractured despite a high level of hardness [50]. This can be caused by decreased elasticity of the sclerotic bone.…”
Section: Intraoperative Fracturementioning
confidence: 99%